Avaliação da secagem do bagaço de cajá usando planejamento fatorial composto central - Silva, Andréia Souto da (2008)
This work deals with the kinetics assay of Cajá (Spondias mombin L.) bagasse drying by an experimental design using a tray dryer. In order to add-value to this product a kinetic study has been carried out. A central composite experimental design has been carried out to evaluate the influence of the operational variables: input air temperature (55; 65 e 75ºC); the drying air velocity (3.2; 4.6 e 6.0 m/s) and the fixed bed thickness (0.8; 1.2 e 1.6 cm) and as response variable the the moisture content (dry basis). The results showed that the diffusional Fick model fitted quite well the experimental data. The best condition found has been input air temperature of 75ºC, drying air velocity of 6.0 m/s as well as fixed bed thickness of 0.8 cm. The experimental design assay showed that the main effects as well as the second ones were significant at 95% confindance level. The best operational condition according to statistical planning was 75 oC input air temperature, 6.0 m.s-1 drying air velocity and 0.8 cm fixed bed thickness. In this case, the equilibrium moisture content (1.3% dry basis) occured at 220 minutes